Imperatyw opieki paliatywnej w medycynie weterynaryjnej - Kuśnierz, Krzysztof (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
One of the main causes of the ethical ambivalence in the attitude of homo sapiens species towards other living creatures is its utilitarian and anthropocentric mindset which permeates practical decisions and judgments. Socio-ecological conditioning of the human-animal relations to which the former contributed through practices and habits (habitus) largely designating the so called cultural norms (at least in Bourdieu’s conception) have thus far legitimized speciesism as well as disablement and exclusion of animals from the advantages of technology and veterinary medicine, which in turn would strengthen their position in the face of continual exploitation in favor of man. Since few decades this state of affairs has been changing; man’s ethical consciousness in respect of the predicament, state of mind and well–being of other living creatures is rising. The encounter of man with different non-human beings who do not know human forms of auto-expression or communication became possible through the discovery of science – as well as philosophy’s and particularly ethics’ indication – of common properties and socio-cognitive capabilities: including fellow feeling which in case of a human being is followed by consciousness, understanding, interpretation, as well as relevant decisions and actions. This common denominator among species is waiting for further exploration and redefinition in terms of ethics. That is exactly what constitutes the requirement for improvement of the condition of other species in the world exploited by human kind. Many academic disciplines contribute to the unceasing widening of the moral horizon (empathy, fellow feeling, responsibility, solidarity, readiness to care and help) so that it could embrace over time as many individuals representing species outside homo sapiens as possible. Veterinary medicine and palliative care create conditions that foster the rebuilding of a caring relationship between man and other living creatures, opening at the same time door to recognition and meaningful relations (in Ricoeur’s terms), understanding and love of the universe of life (bios) that man shares with other species.
Imperative to Palliative Care in Veterinary Medicine
Keywords: anthropocentrism; universe of life; veterinary palliative care; speciesism; recognition; recognition; state of mind; fellow feeling; empathy